Analysis of Water Resources, Public Health, and Economic Development in the Sungai Panas Region of Batam City - Deon Libora; Ade Jaya Saputra (Fakultas Teknik Sipil dan Perencanaan, 2023)
The Sungai Panas area is an area with significant tourism potential due to its natural attractions, including hot springs. However, to make optimal use of this potential, it is important to understand the complex relationship between adequate water resources, good public health, and sustainable economic growth. This analysis includes three main aspects. First, the availability and quality of water resources in the Sungai Panas area plays an important role in maintaining public health and supporting economic activities. Second, good public health is critical to achieving sustainable economic development. Third, the relationship between public health and economic development also needs attention. This analysis underscores the importance of collaborative efforts from various stakeholders, including the government, the private sector, and local communities in managing water resources, improving public health, and promoting sustainable economic development in the Hot River area of ​​Batam City. These efforts include implementing good water management practices, investing in sanitation infrastructure, raising awareness about the importance of water resources and public health, and developing policies that support the synergies between these three aspects.